Potret Istri yang Cakap: Studi Komparasi antara Gambaran Istri dalam Amsal 31:10-31 dengan Gambaran Perempuan (Istri) Jawa - Vincentius Doni Erlangga Satriawan; Nikolas Kristiyanto (Sekolah Tinggi Teologi Intheos Surakarta, 2023)
Abstract. Patriarchal domination often causes gender bias. In this case, woman is considered to be in a subordinate position to man. This impression can also be seen in Javanese culture, in which woman are often seen as “konco wingking.” Therefore, this paper intends to examine the portrait of woman (wife) in Javanese culture by comparing them with the description of woman in Proverbs 31:10-31. This study is conducted by Martha Nussbaum's feminist interpretation. Through this study, an understanding was obtained that as described by woman in Proverbs 31:10-31, woman's position in Javanese culture does not always have to be interpreted as a limitation, but instead becomes a means of woman’s developing and controlling over her environment as the key to achieving happiness.Abstrak. Dominasi patriarki seringkali menyebabkan adanya bias gender. Dalam hal ini perempuan dianggap dalam posisi subordinat dari laki-laki. Kesan tersebut juga terlihat dalam budaya Jawa, di mana perempuan tidak jarang dianggap sebagai “konco wingking.” Oleh karena itu, tulisan ini bermaksud untuk mengkaji potret perempuan (istri) dalam budaya Jawa dengan mengkomparasikan dengan gambaran perempuan dalam Amsal 31:10-31. Studi ini memanfaatkan interpretasi feminis Martha Nussbaum. Melalui kajian ini diperoleh pemahaman bahwa sebagaimana gambaran perempuan dalam Amsal 31:10-31, posisi perempuan dalam budaya Jawa tidak selalu harus dimaknai sebagai pembatasan, namun justru menjadi sarana pengembangan dan kontrol perempuan terhadap lingkungannya sebagai kunci mencapai kebahagiaan.